Food choices and preferences on food systems and food security in Caribbean Small Island Developing States - Daley, Oral O.; Webb, Marquitta; Isaac, Wendy-Ann P.; Wilson, Stefan (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe Caribbean dietary landscape has undergone significant transformation over the past six decades. The events of political independence, coupled with the departure of colonizing countries have led to a cultural shift, characterized by the proliferation of fast-food restaurants. Hence, this study investigates how cultural, economic, and social factors influenced dietary habits in terms of food choices and preferences and how these factors contributed to food security outcomes in the region.MethodsAn online cross-sectional survey was conducted, among consumers from Barbados, Dominica, Jamaica, and Trinidad and Tobago to assess their knowledge of food systems and food security, food choices and preferences, influencers and concerns about food systems.Results and discussionOverall knowledge of food system and food security was significantly associated with marital status (p ≤ 0.012) and household size (p ≤ 0.044). A significant, moderately positive correlation (ρ = 0.631, p < 0.001) was found between food choices and preferences, as well as their influences. This study highlights the need for comprehensive and culturally sensitive approaches to food education and policy development in the Caribbean. By increasing consumer knowledge, addressing concerns about sustainability and food security, and promoting local food production, the region can take significant steps toward building a more resilient and sustainable food system.